Analisis Penerapan Balance Scorecard (BSC) untuk Meningkatkan Kinerja UMKM : Studi Kasus pada UMKM Mie Ayam dan Bakso Cak No - Diva Fanesintya; Rizza Alvia; Renda Febriana; Muhammad Akzail Ilham S; Annisa Herawati; Mochamad Reza Adiyanto (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
Micro, Small and Medium Enterprises or often abbreviated as MSMEs require effective management tools to achieve optimal and sustainable performance. Balance Scorecard is a strategic management system that aims to describe the organization's strategic mission into operational goals and performance benchmarks with various perspectives. This research was conducted on one of the chicken noodle and meatball businesses, namely Cak No's, to analyze the application of the Balance Scorecard for the business he runs. The method used is a mix of methods with data obtained from interviews, observations, and simple business documents The results of the study show that 3 perspectives of the balance scorecard are declared to be achieved. In other words, the Cak No chicken noodle business has a good performance in terms of finances, customers, and internal business processes.